TRAITS OF MASCULINITY AS DEPICTED IN AVENGERS: ENDGAME MOVIE - Puspa Indah Aditya Pratama; Tri Wahyu Retno Ningsih (Jurusan Sastra Indonesia, 2021)
The concept of masculinity has broadened as a result of gender equality. Masculinity refers to a culture in which men's and women's social roles are clearly defined. This research objective was to find out traits of masculinity of male characters in Avengers: Endgame movie based on the theory proposed by David & Brannon, Beynon (2007). The research method used a descriptive qualitative method. The data of this research are dialogues and scenes in Avengers: Endgame movie. The results represent that there were seven traits of masculinity found in the male characters of Avengers: Endgame movie were be a big wheel, be a sturdy oak, give 'em hell, new man as nurturer, new man as narcissist, new lad, and metrosexual men. The researcher also found out the dominant traits of masculinity namely new man as nurturer. Keywords: gender, masculinity, traits of masculinity, movie.